Effect of Supervised Resistance Training on Arm Volume, Quality of Life and Physical Perfomance Among Women at High Risk for Breast Cancer-Related Lymphedema: A Study Protocol for a Randomized Controlled Trial (STRONG-B) - Ramírez-Parada, Karol; Lopez-Garzon, Maria; Sanchez-Rojel, Cesar; Petric-Guajardo, Militza; Alfaro-Barra, Margarita; Fernández-Verdejo, Rodrigo; Reyes-Ponce, Alvaro; Merino-Pereira, Gina; Cantarero-Villanueva, Irene (Frontiers in Oncology, 2022)
Objectives To determine the preventive effects of supervised resistance training on arms volume, quality of life, physical performance, and handgrip strength in Chilean women at high risk for breast cancer-related lymphedema (BCRL) undergoing chemotherapy. Design Randomized control trial. Participants One hundred and six women at high risk for breast cancer-related lymphedema aged 18 to 70 years. Interventions Participants will be randomized into two groups: [a] intervention, who will receive 12 weeks of supervised resistance training (STRONG-B) during adjuvant chemotherapy; and [b] control, who will receive education to promote lymphatic and venous return, maintain range of motion, and promote physical activity. Main Outcome Measures The primary outcome will be arms volume measured with an optoelectric device (perometer NT1000). Secondary outcomes will be quality of life, handgrip strength, and physical performance. Primary and secondary outcomes will be measured at baseline, just after the intervention, and 3 and 6 months after. Statistical analysis will be performed following intention-to-treat and per-protocol approaches. The treatment effect will be calculated using linear mixed models. Discussion The STRONG-B will be a tailored supervised resistance training that attempts to prevent or mitigate BCRL in a population that, due to both intrinsic and extrinsic factors, will commonly suffer from BCRL. Clinical Trial Registration [https://clinicaltrials.gov/ct2/show/NCT04821609], identifier NCT04821609.